Analysis of Profitability and Solvency in Kimia Farma, Tbk Company in 2023-2025 - Astuti Madewi; Achmad Ridwan; Athiy Dina Rosihana; Wawan Saputra; Megania Kharisma (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to analyze the profitability and solvency of PT Kimia Farma Tbk, a state-owned pharmaceutical company listed on the Indonesia Stock Exchange, for the period 2023-2025. The research employs a mixed-method approach combining qualitative and quantitative analysis, utilizing financial ratio analysis derived from the company's audited annual financial statements. Profitability is measured using Gross Profit Margin (GPM) and Net Profit Margin (NPM), while solvency is assessed through Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER). The findings reveal that Gross Profit Margin showed an improving trend, increasing from 31% in 2023 to 30% in 2024 and 33% in 2025, indicating successful cost management and operational efficiency improvements. However, Net Profit Margin remained negative throughout the period, although it showed gradual improvement from -18% in 2023 to -11% in 2024 and -8% in 2025, reflecting narrowing losses due to effective restructuring efforts. In terms of solvency, both Debt to Asset Ratio and Debt to Equity Ratio exhibited consistently increasing trends, rising from 64% to 81% and from 175% to 418% respectively, indicating growing reliance on debt financing and higher financial risk. The study concludes that while Kimia Farma has demonstrated improvement in operational efficiency and profitability margins, the company still faces considerable challenges in managing its debt levels and achieving sustainable net profitability. These findings provide valuable insights for management and stakeholders in making future strategic decisions and highlight the importance of continued financial restructuring and risk management efforts.